2022
DOI: 10.21037/atm-22-4312
|View full text |Cite
|
Sign up to set email alerts
|

Anlotinib combined with chemotherapy and immunotherapy for advanced pulmonary sarcomatoid cancer: a case report and literature review

Abstract: Background: Pulmonary sarcomatoid carcinoma (PSC) is a rare disease which is highly malignant with a poor prognosis. PSC is highly resistant to chemotherapy and radiotherapy and is prone to recurrence even after surgery. Most of what is known about PSC comes from limited single-center, retrospective studies.There is still no standard international clinical guideline for PSC. Limited case reports have shown that PSC patients with driver gene mutations and high programmed death-ligand 1 (PD-L1) expression have g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…PSC is a rare and poorly differentiated NSCLC, which is commonly accompanied by sarcoma or sarcomatoid components, characterized by rapid proliferation, high vascular invasion and epithelial-mesenchymal transition. Many previous case reports have shown that compared with surgical resection or combined chemotherapy, combination therapy with TKIs and ICIs have promising efficacy in patients with PSC, significantly improving the progression free survival (PFS) and overall survival (OS) of patients, and some even achieve PR ( 8 , 11 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PSC is a rare and poorly differentiated NSCLC, which is commonly accompanied by sarcoma or sarcomatoid components, characterized by rapid proliferation, high vascular invasion and epithelial-mesenchymal transition. Many previous case reports have shown that compared with surgical resection or combined chemotherapy, combination therapy with TKIs and ICIs have promising efficacy in patients with PSC, significantly improving the progression free survival (PFS) and overall survival (OS) of patients, and some even achieve PR ( 8 , 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…ICIs can improve the prognosis of patients with advanced NSCLC. The high expression of PD-L1 and proportion of patients with high TMB are relatively common in PSC compared with other subtypes ( 8 ). It has been reported that among PSC patients, over 50% showed positive PD-L1 expression ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“… 104 In another patient with advanced PSC but negative PD-L1 expression, combination therapy with atezolizumab, bevacizumab, carboplatin, and paclitaxel (ABCP) resulted in marked shrinkage of the tumor, and continued shrinkage was observed during maintenance therapy with atezolizumab and bevacizumab. 105 Other combinations, including anlotinib plus tislelizumab 106 or sintilizumab, 107 have also been reported to be effective.…”
Section: Efficacy Of Fda-approved Targeted Therapiesmentioning
confidence: 99%
“…One study showed that patients with PSC treated with chemotherapy combined with immunotherapy as first-line therapy achieved an objective response rate (ORR) of 73.8% and a median progression-free survival (mPFS) of 10.3 months (6). There are also some case reports that the use of targeted drugs significantly alleviates disease and even survival benefits in patients with PSC (7)(8)(9). Thus, immunotherapy and targeted therapy may offer new opportunities for the treatment of PSC.…”
Section: Introductionmentioning
confidence: 99%